Efektivitas Pemberian Pupuk Kandang Sapi dan Eco Enzyme terhadap Pertumbuhan dan Produksi Tanaman Kemangi (Ocimum basilicum L.) - Prayoga Prayoga; Najla Lubis; Desi Sri Pasca Sari Sembiring (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Basil (Ocimum basilicum L.) is a horticultural plant widely used as a fresh vegetable and herbal ingredient. Efforts to increase basil growth and production can be achieved through environmentally friendly organic fertilization, one of which is the use of cow manure and eco- enzymes. The purpose of this study was to determine the response due to the provision of eco enzyme and cow manure on the growth and production of basil plants. This research method used a factorial randomized block design (RAK) with two factors. The first factor was the provision of cow manure with 4 levels, namely S0 = no treatment, S1 = 200g, S2 = 300g, S3 = 400g. The second factor was the provision of EE with 4 levels, namely E0 = no treatment, E1 = 10ml, E2 = 20ml, E3 = 30ml. The observation parameters of this study were plant height, stem diameter, number of primary branches, fresh weight, root length, flowering age. The results of this study are expected to provide recommendations for effective organic fertilization to increase basil plant productivity sustainably.